Pengembangan Perangkat Model Pembelajaran Berbasis Masalah Berbantuan Media Kotak Kartu Misterius (KOKAMI) Untuk Meningkatkan Kemampuan Pemecahan Masalah Fisika Peserta Didik - Tegar Agusfian Mandiri; Muhammad Zuhdi; Ni Nyoman Sri Putu Verawati (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2021)
This study aims to produce appropriate and effective learning tools based problem-based learning model assisted by media kotak kartu misterius (KOKAMI) to improve students' problem solving skills in Physics. This study uses Research and Development (RnD) research with a 4D model consisting of four stages, namely Define, Design, Develop, and Disseminate. The tools developed in this study were the syllabus, lesson plans, LKPD, analysis of learning materials, problem solving ability test instruments, and KOKAMI learning media. The feasibility of the developed device was obtained based on the validity and reliability of the learning device. The validity of the developed device was obtained from a questionnaire assessment of six validators, namely three expert validators and three practitioner validators, then the validity of the device was analyzed using a Likert scale. The reliability of the developed device was obtained from the calculation of the percentage of agreement (PA) from the questionnaire assessment by six validators. The effectiveness of the device is obtained based on the analysis of the acquisition of N-Gain scores obtained from the assessment of the problem-solving ability test carried out by 15 students. Based on the results of the research that has been done, the average value of expert validity is 3.43 and practitioner validity is 3.68 in the very good category, then the average reliability of the device by expert validity is 91.83% and practitioner validity is 93.71% which indicates the device can be said to be reliable. Analysis of the calculation of the effectiveness of the developed device shows the acquisition of the N-Gain value in a limited trial obtained an average of 0.63 which indicates the medium category. So it can be concluded that the learning tools developed are effective.